Women and the Reformations: Reflections on Recent Research - Wiesner, Merry E. (History compass, 2004)
Scholarship on women and the Protestant and Catholic Reformations over the last quarter-century has stressed diversity, difference, and complexity. It has developed new theoretical and methodological directions, and also presented new ways to look at more "old-fashioned topics," such as the lives of great women and the ideas of great men. Many studies have explored women's actions in support of or in opposition to the Protestant and Catholic Reformations and women's spirituality more broadly; among these, research on convents and female religious has been especially innovative. Studies of the ideas of the reformers and the effects of the Reformations on women, the family, and notions of gender have focused particularly on the process of social discipline, noting continuities with medieval patterns as well as new emphases. The focus on the "long Reformation" and increased attention to the expansion of Christianity beyond Europe, represent burgeoning areas of current research.